Physical, chemical and microbiological properties of different combination of soilless media and their effect on the vegetative component and nutrient content of hempedu bumi (Andrographis paniculata) - Ali, Shara Salih; Sakimin, Siti Zaharah; Othman, Radziah; Megat Wahab, Puteri Edaroyati (Universiti Putra Malaysia Press, 2017)
Soilless media (SM) is a common worldwide growing method for industrial horticultural production. It is a good growing medium that relies on the properties that benefit plant growth i.e. physical property, chemical properties and microbial activity. There are several SM with good characteristics such as empty fruit bunch compost (EFBC), coconut coir dust (CCD) and peat. EFBC is one of the organic residues of oil palm that provide beneficial microorganisms a good source of bacteria-rich, high nutrient content. The composting process reduces the pH of EFB by 6.86-7.20 to 4.5-6.0. CCD is recommended as a substitute for other media because of it is excellent for holding water and drainage and has high air porosity due to its large surface area. Microbiologically, CCD is the absence of weeds and pathogens and has anti-fungal properties that prevent soil-borne diseases. It also maintains greater oxygen levels and is reusable after sanitisation. Despite the ideal characteristics of CCD, there are some chemical limitations of this medium, including low pH and low potassium content. Peat has good aeration characteristics that are good for root growth. An experiment was conducted to evaluate the best medium combinations for growth performance and nutrient content of hempedu bumi (Andrographis paniculata). Three types of SM with five different combinationa were used as growing media for the plant; they included C1=CCD (1: -) as control; C2=EFBC + CCD (7:3); C3=EFBC + CCD (3:7); C4=CCD + Peat (7:3) and C5=CCD + Peat (3:7). Prior to the experiment, the physical, chemical and microbiological properties of the media were determined. The experiment was conducted in RCBD with five replications. In this experiment, the parameters of vegetative components (plant height, number of leaves and total leaf area), dry matter yield and partitioning [root, shoot dry weight and root to shoot ratio (R:S)] and the macronutrient nitrogen [(N), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg)] of hempedu bumi were determined. C3 showed the highest vegetative component [plant height (39.5 cm), number of leaves (72.7 leaf plant-1), total leaf area (79.8 cm2) and shoot dry weight (3.03 g)] of hempedu bumi. The highest macronutrient content (1.17% N, 0.07% P, 2.45% K, 2.77% Ca and 0.58% Mg) was in the leaf tissues of hempedu bumi when grown in the C3 media. In conclusion, a combination of EFBC+CCD (3:7) is recommended as a suitable growing medium for hempedu bumi due to the greater vegetative components well as the higher macronutrient content it yielded in the leaf tissues of the plant.